The enchantment of sukuk yield, BI rate, and inflation on the trading volume of sukuk retail SR014 - Astutik, Rahayu Puji; Utama, Yopi Yudha; Weny, Siska Yulia; Hariyani, Happy Febrina (Universitas Muhammadiyah Malang, 2026)
Purpose: Retail Sukuk SR014 is a sukuk that has the lowest coupon throughout the series of SBN issuances, despite the trend of rising yields in the SBN market in the current year of 2021. This research was conducted to determine whether yield, inflation, and the BI rate affect the trading volume of retail sukuk SR014. Methodology/approach: This research uses a quantitative research method. The population in the study is retail sukuk (SR014). The sampling technique used was saturated sampling. The sample in this study is the retail sukuk SR014 for a period of 34 months. The data analysis technique used is multiple linear regression using the SPSS program. Findings: Based on the results of the partial test, the yield and inflation variables have a significant negative impact on the trading volume of retail sukuk. In the BI rate variable, there is no significant positive effect on the trading volume of retail sukuk. This can happen because the BI rate is not the main factor influencing investors to buy retail sukuk. Meanwhile, the results of the simultaneous test on the yield, inflation, and BI rate variables have an impact on the trading volume of retail sukuk. Practical implications: For investors, it is important to pay attention to the yield offered by retail sukuk as well as the prevailing inflation conditions when deciding to invest. A high yield tends to provide more attractive returns, but it must be balanced with an understanding of inflation that can erode the real returns of the investment instrument. Originality/value: This research is expected to contribute by enhancing understanding of the factors influencing the trading volume of sukuk, such as yield, inflation, and the BI Rate